Comparison of Stress Coping Styles, Defense Mechanisms, and Type D Personality in Patients with Psoriasis and Seborrheic Dermatitis and Healthy Individuals - Falizi, Anahita; Golshani, Fatemeh; Eftekhari, Hojjat (Mental Health and Lifestyle Journal, 2023)
The present study aimed to compare stress coping styles, defense mechanisms, and Type D personality in patients with psoriasis, seborrheic dermatitis, and healthy individuals. This causal-comparative study included patients with psoriasis and seborrheic dermatitis who visited the Razi Specialized and Subspecialized Dermatology Clinic in Rasht during the spring of 2021. From this population, 60 patients with psoriasis or seborrheic dermatitis and 30 healthy individuals, who were companions of the patients, were selected through convenience sampling. Data were collected using the Stress Coping Styles Questionnaire (Lazarus & Folkman), the Defense Style Questionnaire (Andrews et al.), and the Type D Personality Scale (Denollet). Data analysis was performed using one-way analysis of variance (ANOVA) in SPSS version 2023. The results indicated significant differences among the groups in emotion-focused coping style (F = 38.88, p = .001), neurotic defense mechanisms (F = 69.91, p = .001), immature defense mechanisms (F = 27.25, p = .001), and the Type D personality components of negative affectivity (F = 3.96, p = .022) and social inhibition (F = 112.59, p = .001). The findings of this study suggest that differences in coping styles, defense mechanisms, and Type D personality components may play an important role in the development and persistence of psychological responses in dermatological patients. In other words, distinct personality and emotional patterns among individuals with psoriasis and seborrheic dermatitis may influence how they experience and manage disease-related stress.